2017
DOI: 10.4269/ajtmh.16-0479
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Echinococcosis Among Schoolchildren in Golog Tibetan Autonomous Prefecture, Qinghai, China

Abstract: Echinococcosis is a serious zoonotic parasitic disease that is highly endemic in Qinghai Province. The present study aimed to investigate the prevalence of echinococcosis among schoolchildren in Golog Tibetan Autonomous Prefecture to improve early diagnosis and treatment of patients and to provide information for echinococcosis prevention and control. A total of 11,260 schoolchildren from five counties (Maqin, Gander, Dari, Jiuzhi, and Banma) in Golog Tibetan Autonomous Prefecture, Qinghai Province, were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
1
22
2
Order By: Relevance
“…Such observation has been reported in some of the previous studies. 7,28,29 For instance, a retrospective analysis of hospital records of children with hydatid cyst in the south of Iran showed that the frequencies of hydatid cyst in females (56.1%) are higher than males (42.1%). 30 Contrary to our findings, studies by Mamishi et al and also Aslanabadi et al in Iran and Kandeel et al in Egypt reported a higher prevalence of hydatid cyst in males.…”
Section: Discussionmentioning
confidence: 99%
“…Such observation has been reported in some of the previous studies. 7,28,29 For instance, a retrospective analysis of hospital records of children with hydatid cyst in the south of Iran showed that the frequencies of hydatid cyst in females (56.1%) are higher than males (42.1%). 30 Contrary to our findings, studies by Mamishi et al and also Aslanabadi et al in Iran and Kandeel et al in Egypt reported a higher prevalence of hydatid cyst in males.…”
Section: Discussionmentioning
confidence: 99%
“…AE has been a public health concern in northern Japan for the past 40 years (20)(21)(22). Mass screening with ultrasound (US) and serology in China have confirmed a high incidence of AE on the Tibetan plateau (in Qinghai, Sichuan, and Tibet [23]) and show that AE prevalence, especially in children, is higher than that of CE in several areas (24). Among the 18,235 estimated new AE cases per year globally, 91% occur in China 7, with human prevalence of Ͼ3% in some areas (25).…”
Section: Epidemiology and Transmission Distribution Of Ce And Aementioning
confidence: 99%
“…Overall, the figures are unchanged and no recent spread, increase, or decrease of case numbers has been described by authors publishing Chinese data. The high prevalence in schoolchildren is particularly remarkable, as paediatric cases of disease are absolute rarities in other parts of the world [86][87][88].…”
Section: Asiamentioning
confidence: 99%
“…Schoolchildren, 6-16 years + + + n/a n/a n/a n/a Cai [86] Qinghai (Yushu and Children, 6-12 years/ Tibetan rural population + + + n/a n/a n/a n/a Han [154] Qinghai (Huangnan Prefecture) 29 1150…”
mentioning
confidence: 99%